Modelo de gestión de calidad basado en el enfoque holístico y clima organizacional en la Institución Educativa Carlos Olivares, Chepén - Lopez Perez, Carlos Alberto (2019)
Investigation had like purpose to know how the application of a high-quality management model has influence, once the holistic focus was based on, for the better significantly the organizational climate of the Educational Institution N 80382 Carlos A. Olivares. The size of the sample was shaped by the administrative and staff's on duty 11 members, the senior staff's 51 members and teacher and 50 students. As the instrument of previous and later measurement used a test on the organizational climate itself. Results evidence than: The level of organizational climate in the administrative and workers on duty, according to the pre test is deficient in a 72.7 % and according to he behind test is good in a 63.6 %. The level of organizational climate in the senior staff and teacher, according to the pre test is deficient in a 54.9 % and according to he behind test is fairly good in a 49 %. The level of organizational climate in the students, according to the pre test is deficient in 60 % and according to he behind test is 40 prone % fairly goodly to good 20 %. Statistically significant difference between the scores exists before and after application the management model once the holistic focus in the improvement of the organizational climate in the administrative and workers on duty was based on, in the senior staff and teacher and in the Educational Institution's students N 80382 Carlos A. Olivares of Chepén.